UNIVERSITY INNOVATION COOPERATION WITH BUSINESS COMMUNITY - Tatyana M. Davydenko (Высшее образование в России)
The article analyzes the trends and mechanisms of interaction between businesses and Voronezh State University. It also presents good practices of implementation of joint projects in the sphere of high-tech industries and in-service training of engineers and technical staff.